2020
DOI: 10.1111/jopy.12542
|View full text |Cite
|
Sign up to set email alerts
|

Hurricane exposure and personality development

Abstract: ObjectiveWe evaluated the role of natural disaster adversity on personality development in the wake of a hurricane, and the moderating role of previous hurricane exposure.MethodWe used a two‐wave longitudinal design and a diverse sample of emerging adults (n = 691; mean age = 22 years; 72% females, 27% European American, 29% Latino, 23% Asian American, 15% African American, 6% Multiracial/Other) who were exposed to one of the most damaging hurricanes on record, though to differing degrees. Immediately after th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 55 publications
3
14
0
1
Order By: Relevance
“…Chopik et al (in press) also found that the remaining soldiers were resilient in the wake of deployment; that is, their character strengths remained stable post‐deployment. This stability in personality characteristics echo the findings of Damian et al (in press) and Rakhshani and Furr (in press), who found evidence for stability in diverse community samples. Damian found that people's personality states remained resilient in the wake of a natural disaster, whereas Rakhshani and Furr found evidence for personality traits predicting the subsequent experience of adversity.…”
supporting
confidence: 88%
“…Chopik et al (in press) also found that the remaining soldiers were resilient in the wake of deployment; that is, their character strengths remained stable post‐deployment. This stability in personality characteristics echo the findings of Damian et al (in press) and Rakhshani and Furr (in press), who found evidence for stability in diverse community samples. Damian found that people's personality states remained resilient in the wake of a natural disaster, whereas Rakhshani and Furr found evidence for personality traits predicting the subsequent experience of adversity.…”
supporting
confidence: 88%
“…Natural experiments allow researchers to examine the effects of exogeneous shocks -defined as unexpected or unpredictable events that are outside of the participants' and researcher's control -on psychological variables while ruling out third-variable or reverse causality explanations (Akee et al, 2018). Major collective events such as natural disasters (e.g., Damian et al, 2021) create natural experiments because they meet the aforementioned criteria and affect many people at once. For example, recent studies have begun to examine the effects of the Covid-19 pandemic on changes in personality traits and well-being (e.g., Sutin et al, 2020).…”
Section: Natural Experimentsmentioning
confidence: 99%
“…The third study found no significant changes in the Big Five trait levels or their rates of change in Huston students a year after they were exposed to Hurricane Harvey in 2017 (Damian et al, 2021). Notably, none of these studies considered to what extend different individuals were personally affected by the respective disasters, which might explain the lack of notable changes.…”
Section: The Thematic Facetmentioning
confidence: 94%
“…For example, hurricanes can only occur in the Atlantic, they are about 300 miles wide and across its different parts-outflow, feeder bands, eyewall, eye, and the storm surge-its destructive powers can vary dramatically. Thus, location can be important to determine who has been more or less exposed to some collective life event like a hurricane (Damian et al, 2021;Mancini et al, 2021). Moreover, topographical features like mountains can attract and foster individuals of a specific personality profile (Götz et al, 2020).…”
Section: The Spatial Facetmentioning
confidence: 99%